Advances in turfgrass weed management - Elmore, Matthew T. (Burleigh Dodds Series in Agricultural Science, 2023)
Weeds are a major pest that reduce aesthetics and functionality of turfgrass systems. Knowledge required for effective weed management has evolved in recent years as weeds develop resistance to herbicides, government restriction of broad-spectrum herbicides has increased, and registration of new herbicide active ingredients has slowed. This chapter discusses relevant and recent developments in synthetic herbicides, alternatives to synthetic herbicides, and non-chemical strategies for weed management including cultural, physical, and genetic approaches. Advances in integrated weed management strategies and barriers preventing adoption of integrated weed management strategies are also discussed. Opportunities for research and development to improve integrated weed management are presented throughout.